LINGUODIDACTIC BASIS OF THE FORMATION OF FOREIGN LANGUAGE COMPETENCE OF THE SCHOOLCHILDREN IN THE CONDITIONS OF MULTILINGUISM (ON THE EXAMPLE OF GERMAN SPEAKING COUNTRIES) - Лариса Купчик (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
basis of the analysis of language didactic approaches of foreign language teaching at the end of the XX - the beginning of the XXI century in schools of German-speaking countries it highlights the dissemination of communicative language didactics. Besides, the author distinguishes the key principles of modern foreign language didactics, such as learner autonomy, cooperative learning, authentic teaching material. It is highlighted in the article that early foreign language learning stimulates the use of playing methods and their use is advantageous at foreign language lessons. The plurilingualism of society brings changes into foreign languages teaching as the language repertoire of pupils has increased, namely: the formula "mother tongue + two foreign languages" has been introduced in the schools of German speaking countries that foresees the use of tertiary language didactics.